Case Study of the Excessive Vibration of the Medium and High Speed Motors in Circulating Water Filtration System. Issue 1 (November 2020) - Yuan, Liang; Bai, Jinchuan; Feng, Bo; Wan, Li; Chen, Songping; Chen, Hanbin
Abstract: In one Chinese nuclear power plant, the problem of excessive vibration of medium and high-speed motors(MHMs) in the Circulating Water Filtration System (CFI) frequently occurred during the reactor power operation level. Excessive motor vibration caused the motors to trip, further causing the CFI to shut down automatically. Through a series of theoretical studies and experimental demonstrations, this paper finds out the root cause of excessive vibration of MHMs. The reason is that there are defects in the design and installation of motors, and the motors' installation methods do not meet the operating requirements. To solve the problem, we designed a support frame with adjustable supporting forces and determined its optimal supporting force through a large number of experiments. Compare the motors' vibration data before and after the installation of the support frame, and it can see that the support frame fundamentally solves the problem of high vibration of MHMs, and improves the reliability and safety of the units. The support frame designed in this paper also provides a good demonstration of solving similar problems.